Odpowiedzi

2010-02-08T18:56:52+01:00
A) 1/2 ( x+3)=2x-4 |×2
x+3=4x-8
3+8=4x+x
5x=11 |÷5
x=11÷5
x=2,2

b) 3(x+2)-7(2-3x)=8(x-3)
3x+6-14+21x=8x-24
24x-8x=-24+8
16x=-16 |÷16
x=-1

c) 3- 2x+3/2 = 17/9 - 3x+2/2

d) 2- 4x-5/5=1,9 - 1-x/2

e) 4/x+9 = 2/2x-3

f)2x-5/x+1= 5/3

g) 2(x+5)/4=5(3-x)/8 |×8
4x+20=15-5x
9x=-5|÷9
x=-9/5
2010-02-08T18:59:38+01:00
A). 1/2 (x+3) = 2x-4
1/2x +1,5=2x-4
1/2x -2x=-4-1,5
-1,5 x= -5,5 / -1,5
x = 3,6

b). 3 (x+2) - 7 (2-3x) = 8 (x-3)
3x + 6 -14+21x = 8x - 24
3x + 21x - 8x = -24 +14 - 6
16x = -16 / 16
x = -1

c). 3- 2x+3/2 = 17/9 - 3x+2/2
54 - 18x - 27 = 34 - 27x - 18
-18x +27x = - 18 +34+27 - 54
9x = -11 / 9
x - -11/9

d).2- 4x-5/5=1,9 - 1-x/2
20 - 8x +50= 19 - 5 +5x
-8x - 5x= 19-5 -20 - 50
-13x = -56 / -13
x = -4,3